v.2 - "Boersema, Davi" (New Delhi, 2014)
.a lucid, widely accessible overview...Recommended. $1 (BChoice We all face philosophical questions and concerns every day. Far from being abstract and subjective, philosophy is fundamental not only to what we do with our lives, but also to who we are and who we hope to be. The new, four-volume Viva-Facts On File Handbook of Philosophy set provides an accessible and engaging introduction to this important subject. Authors David Boersema and Kari Middleton are academic philosophers who specialize in teaching their subject to beginning philosophical students. Ideal for students and scholars, this set provides a comprehensive survey of philosophy, and each book features an index, an appendix, a bibliography, and a glossary.s
Keywords: "Philosophy, Middleton, Kari, ed"